Haunting memories of the revolution: Hope and despair in East German Lives - Andrews, Molly (PINS-Psychology in Society, 2024)
This paper uses the arguments set out in Bhekizizwe Peterson’s article “Spectrality and inter-generational black narratives in South Africa” as a framework to explore East German narratives of transformational change over the past 30 years, based on interviews with key anti-state activists. Of particular relevance for the East German case are Peterson’s commentaries on 1) contrasting the ‘limitless hope’ of the revolution with subsequent experiences of mourning and melancholia – “unresolved grief” and a nostalgia for a future that once could have been; 2) the exploration of relationship between history, the arts and knowledge; 3) the struggle over creating a national ‘good story’ and the memories that haunt across generations; and 4) the role of radical imagination in social change. Although the presentation will draw on the larger longitudinal project, it will also incorporate a discussion of Lola Arias’s play “Atlas des Kommunismus” which offers a retrospective look at the legacy of communism thirty years after the fall of the Berlin Wall, with characters playing themselves.